Liposomes as carriers for systemic delivery of salmon calcitonin by inhalation - Swaminathan, Janani (Trinity College (Dublin, Ireland). School of Pharmacy & Pharmaceutical Sciences, 2011)
The concept of delivering proteins and peptides to the systemic circulation via the lungs has been extensively investigated over the last 20 years. Main drivers for the approach are the lungs’ high surface area, presumed low activity of metabolising enzymes, quick onset of action and improved patient compliance due to the ability of non-invasive delivery. In addition, less frequent dosing might be possible, if a sustained release delivery system was developed. One of the candidate peptides that have been studied for pulmonary delivery is salmon calcitonin (sCT). Liposomes are carrier systems that have been used for more than 40 years for both drug and protein/peptide delivery, with commercially successful products of, e.g., doxorubicin and amphotericin B. Whilst liposomes containing sCT for parenteral, oral and intranasal delivery have already been reported, liposomal systems for pulmonary sCT delivery have not been reported to date.
Keywords: Pharmacy, Ph.D.; Ph.D. Trinity College Dublin